2022
DOI: 10.3390/jcdd9050162
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity a Risk Factor for Carotid Atherosclerotic Disease?—Opportunistic Review

Abstract: Obesity is a risk factor for coronary atherosclerosis. However, the influence of adipose tissue in carotid atherosclerosis is not completely understood. No systematic review/meta-analysis was previously performed to understand if obesity is a risk factor for carotid atherosclerosis. This paper aims to provide an opportunistic review of the association between obesity and carotid atherosclerosis and define the role of the different adipose tissue depots in the characteristics of carotid stenosis. The databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
(190 reference statements)
1
6
0
Order By: Relevance
“…This research shows the importance of detecting the MONW phenotype in individuals from the general population due to their risk of HBP intervening early in their lifestyle. The mechanisms to explain the association of MONW and hypertension go beyond the increase in fat linked to the increase in BMI, chronic diseases could be further related to the accumulation of intraorganic fat, which can induce the development of hypertension through various mechanisms that lead to chronic systemic inflammation and oxidative stress in obesity such as hyperactivation of the sympathetic nervous system, increased action of the renin angiotensin aldosterone system, changes in the structure and function of the left ventricle [21], chronic vascular inflammation [28], insulin resistance [29] and consequent endothelial dysfunction [10,30].…”
Section: Results Interpretationmentioning
confidence: 99%
“…This research shows the importance of detecting the MONW phenotype in individuals from the general population due to their risk of HBP intervening early in their lifestyle. The mechanisms to explain the association of MONW and hypertension go beyond the increase in fat linked to the increase in BMI, chronic diseases could be further related to the accumulation of intraorganic fat, which can induce the development of hypertension through various mechanisms that lead to chronic systemic inflammation and oxidative stress in obesity such as hyperactivation of the sympathetic nervous system, increased action of the renin angiotensin aldosterone system, changes in the structure and function of the left ventricle [21], chronic vascular inflammation [28], insulin resistance [29] and consequent endothelial dysfunction [10,30].…”
Section: Results Interpretationmentioning
confidence: 99%
“…In the present study, BMI and WC were significantly associated with CAS severity. Ferreira et al [ 8 ] also reported a link between obesity and other carotid atherosclerotic plaque characteristics, showing that carotid plaque instability was linked to overall obesity and an increase in fat mass. Similarly, Salari et al [ 36 ] found that moderate to severe atherosclerosis affected 62% of the adult population of northern Iran and was correlated with obesity indices.…”
Section: Discussionmentioning
confidence: 99%
“…The extent and severity of coronary artery plaques and the incidence of major adverse cardiac events are inversely correlated with increased abdominal fat tissue/subcutaneous fat tissue ratio [ 3 , 6 ]. Nevertheless, the impact of obesity on carotid atherosclerosis disease is still under observation [ 7 ], and there is limited research on the effect of adipose tissue on carotid artery atherosclerosis and the risk of stenosis [ 8 ]. Smoking has long been recognized as a major contributor to clinical CVD and is associated with the development of atherosclerosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…showed that there was no association of overall obesity or visceral obesity with the presence of carotid plaque [20,21]. Research by Kim Tae Nyun et al showed the ratio of muscle to fat to be associated with arterial stiffness [22].…”
Section: Introductionmentioning
confidence: 99%